2016
DOI: 10.1080/14733285.2016.1160030
|View full text |Cite
|
Sign up to set email alerts
|

‘You shouldn't blame religion … but the person’ – the ethnic boundary work of young second-generation migrants in Rotterdam

Abstract: In the Netherlands, as in most other western European countries, the desirability and the governability of a multicultural society are topics of debate. In the last decade, this debate has increasingly centred on second-generation migrants, focusing on their high rates of crime and school drop-out. In the Dutch context, however, little scholarly research has paid attention to second-generation migrants' own experiences. In this paper, I therefore focus on the perceptions of ethnic boundaries held by 12-to 19-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Of course, a lot of boundary making happens in educational contexts, some of which may also be openly ethnicising (e.g. Duemmler et al., 2010; Visser, 2016). Overwhelmingly, however, professional educational boundary making primarily implies other forms of categorisation, such as grading students, assessing behaviour or diagnosing learning disorders.…”
Section: Statistical Classification and Educational Boundary Makingmentioning
confidence: 99%
“…Of course, a lot of boundary making happens in educational contexts, some of which may also be openly ethnicising (e.g. Duemmler et al., 2010; Visser, 2016). Overwhelmingly, however, professional educational boundary making primarily implies other forms of categorisation, such as grading students, assessing behaviour or diagnosing learning disorders.…”
Section: Statistical Classification and Educational Boundary Makingmentioning
confidence: 99%
“…When young people were for instance asked to list the most important ‘groups’ in their community, they found this very difficult. Many indicated that such groups did not really exist and when certain groups were identified those were often based on various kinds of subcultures (dancers, soccer players, basketball players), the school they went to, or the sub‐neighbourhood they were from (Visser ). Several of the young people indicated that others were welcome to join their group of friends irrespective of ethno‐cultural background.…”
Section: Perceptions Of Neighbourhood Diversitymentioning
confidence: 99%
“…This study joins a handful of others that have explored how young citizens in culturally diverse nations are navigating diversity, experiencing belonging and expressing their citizenship (Erdal, 2019;Erdal & Strømsø, 2021;Harju, 2018;Valentine, Sporton, & Nielsen, 2009;Visser, 2016;Wang, 2018;Wang & Collins, 2016;Witten, Kearns, Carroll, & Asiasiga, 2019;Wood & Homolja, 2021). However, while such studies have documented the complex 'ethnic boundary work' (Visser, 2016) undertaken by young ethnic minority youth in order to 'fit in' or belong to the nation, very few consider how such young people themselves might reshape the nation (Erdal & Strømsø, 2021;Thompson, 2001;Wilson, 2015).…”
Section: Introductionmentioning
confidence: 99%